Fine mapping of the GWAS loci identifies SLC35D1 and IL23R as potential risk genes for leprosy. Issue 3 (December 2016) - Li, Guo-Dong; Wang, Dong; Zhang, Deng-Feng; Xiang, Qun; Feng, Jia-Qi; Li, Xiao-An; Li, Yu-Ye; Yao, Yong-Gang
Highlights: Rs3762318 and rs2144658 were significantly associated with multibacillary leprosy. SNPs in high LD with rs3762318 and rs2144658 are eQTLs of SLC35D1. SLC35D1 mRNA expression was significantly decreased in leprosy skin tissues. Rare damaging missense variants in IL23R were enriched in leprosy patients. SLC35D1 and IL23R might be leprosy risk genes in Han Chinese. Abstract: Background: Previous genome-wide association study (GWAS) identified two new leprosy associated loci (1p31.3 [rs3762318] and 6q24.3 [rs2275606]). However, there were insufficient validations in independent populations. Objective: To validate the association and to map the potentially causal variants/genes underlying the association between the confirmed GWAS hit and leprosy. Methods: We genotyped 10 variants in the regions encompassing the two loci in 1110 Han Chinese subjects with and without leprosy, followed by expression quantitative trait loci (eQTL), mRNA expression profiling, and network analysis. We further sequenced the exon region of four genes that were located in the confirmed GWAS hit region in 80 leprosy patients and 99 individuals without leprosy. Results: We validated the positive association of rs3762318 with multibacillary leprosy ( P = 7.5 × 10 −4 ), whereas the association of rs2275606 could not be validated. eQTL analysis showed that both the GWAS locus rs3762318 and one surrounding positively associated SNP rs2144658 ( P = 1.8 × 10 −3 ) significantly affected the mRNA expression of a nearby gene SLC35D1, which might be involved in metabolism. Moreover, SLC35D1 was differentially expressed in skin tissues of leprosy patients, and the differential expression pattern was consistent among leprosy subtypes. Rare damaging missense variants in IL23R were significantly enriched in leprosy patients. Conclusion: Our results supported the positive association between the GWAS reported rs3762318 and leprosy, and SLC35D1 and IL23R might be the causal genes.